Analisis Yuridis Tanggung Jawab BPN Kabupaten Wajo Terhadap Pendaftaran Sertifikat Hak Milik Obyek Yang Sedang Berperkara - Sulaeman; Reski Aulia; Besse Muqita; Fadel Muhammad; Firman (YP-SDI Lamaddukelleng, 2025)
This study examines the legal responsibility of the National Land Agency (BPN) of Wajo Regency regarding the issuance of Land Ownership Certificates (SHM) for land still under dispute at the Sengkang District Court. The study employed qualitative methods with a normative and empirical juridical approach. Data were obtained through document studies, interviews with BPN officials, and field observations. The results indicate that the BPN has not fully implemented the principle of prudence in the land registration process. Certificates for land still under legal process are issued without adequate verification with relevant agencies such as the court or village government. Verification is often based solely on documents from the applicant without confirmation of the dispute status. This creates potential conflict, overlapping rights, and undermines legal certainty. The study concludes that the BPN's legal responsibility has not been optimally implemented, both administratively, procedurally, and substantively. The implications of this study are the need to strengthen the verification system, improve inter-agency coordination, and comprehensively evaluate land registration procedures to prevent new disputes and create a transparent and accountable land system.